2018
DOI: 10.1073/pnas.1719551115
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cancer and tumor microenvironment subtyping using confocal infrared microscopy for all-digital molecular histopathology

Abstract: SignificanceCancer alters both the morphological and the biochemical properties of multiple cell types in a tissue. Generally, the morphology of epithelial cells is practical for routine disease diagnoses. Here, infrared spectroscopic imaging biochemically characterizes breast cancer, both epithelial cells and the tumor-associated microenvironment. Unfortunately, conventional spectral analyses are slow. Hence, we designed and built a laser confocal microscope that demonstrates a high signal-to-noise ratio for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 56 publications
3
122
0
Order By: Relevance
“…For a single image, we estimate that the presented upconversion system is in the order of 500 times faster than the FTIR system when using 4-8 mW of incoherent mid-IR light incident on the sample. The number of images needed for computer-assisted classification of biopsies may be as low as 10-20 [36], suggesting that a continuous spectrum is not required. A small number of images will, therefore, favor the upconversion system for this application.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a single image, we estimate that the presented upconversion system is in the order of 500 times faster than the FTIR system when using 4-8 mW of incoherent mid-IR light incident on the sample. The number of images needed for computer-assisted classification of biopsies may be as low as 10-20 [36], suggesting that a continuous spectrum is not required. A small number of images will, therefore, favor the upconversion system for this application.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Moreover, for HSI, large data storage and complex postprocessing software is currently needed to transform raw data into useful information [14]. Recent developments in mid-IR hyperspectral microscopy include tunable quantum cascade laser (QCL) illumination combined with either raster scanning [15] or microbolometer array detectors [16]. These systems have shown their potential to outperform FTIR systems for special applications; however, they still rely on direct detection of the mid-IR signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectroscopic imaging is based on the molecular vibration of materials and has been widely used for chemical identification and analysis based on the characteristic spectra of materials in the infrared frequency region. Because most materials show unique spectra in infrared range, IR spectral imaging has shown the great usefulness as an important analytical tool, especially in chemical and biological imaging . The advances of IR spectral imaging have thus been pushed over years, and as a mature technique, there are many types of Fourier‐transform infrared spectroscopy (FTIR)‐based commercial products.…”
Section: Spectroscopic Imagingmentioning
confidence: 99%
“…By tuning to a molecular absorbance wavelength of interest, real-time molecular imaging can be utilized for immediate unstained tissue analysis. Furthermore, for advanced spectral predication of disease, the Bhargava group has shown that using a confocal Agilent microscope with a QCL source coupled to a Mercury Cadmium Telluride (MCT) detector it was possible to screen automatically breast tissue biopsies (1 mm diameter) in ~1 hour, in High Definition [21].…”
Section: Introductionmentioning
confidence: 99%